Accusatorial and information-gathering interview and interrogation methods: a multi-country comparison - Miller, Jeaneé C. (Psychology, crime & law, 2018)
Suspect interviewing and interrogation practices have been studied in many different countries, including those in North America, Europe, Asia, and Australia. These studies have produced useful and interesting findings, while also leaving an opening for future inquiry. Specifically, previous research has noted that we might expect interrogation and interviewing practices to vary among different countries or regions, due to distinct approaches to suspect questioning. However, to our knowledge, few previous studies have examined the comparative use of tactics, techniques, and procedures employed to elicit confessions and information from criminal suspects across multiple countries. In the present study, using a consistent survey, we contrasted the interviewing and interrogation practices of 185 practitioners from America, Canada, and Europe, Australia, and New Zealand. In large part, we found that American and Canadian interrogators were similar to one another, and conformed to an accusatorial approach (in both deception detection and questioning techniques). In contrast, interviewers from Europe, Australia, and New Zealand conformed more to an information-gathering approach.